2014
DOI: 10.1039/c4nr00454j
|View full text |Cite
|
Sign up to set email alerts
|

Bottom-up synthesis of nitrogen-doped graphene sheets for ultrafast lithium storage

Abstract: A facile bottom-up strategy was developed to fabricate nitrogen-doped graphene sheets (NGSs) from glucose using a sacrificial template synthesis method. Three main types of nitrogen dopants (pyridinic, pyrrolic and graphitic nitrogens) were introduced into the graphene lattice, and an inimitable microporous structure of NGS with a high specific surface area of 504 m(2) g(-1) was obtained. Particularly, with hybrid features of lithium ion batteries and Faradic capacitors at a low rate and features of Faradic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
100
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(103 citation statements)
references
References 70 publications
2
100
1
Order By: Relevance
“…The excellent conductivity of PGS-2-1000 can generate excellent high-rate performance and superior cycle lifetime. The excellent electrochemical performance of PGS-2-1000, which could be attributed to its unique microstructure, presents the following advantages: (1) The porous structure may act as a reservoir for Li + ions storage and is optimal for the easy immersion and diffusion of the electrolyte, which can shorten the path lengths with less resistance for both Li + ion diffusion and electron transport within the electrolyte [73];…”
Section: Resultsmentioning
confidence: 99%
“…The excellent conductivity of PGS-2-1000 can generate excellent high-rate performance and superior cycle lifetime. The excellent electrochemical performance of PGS-2-1000, which could be attributed to its unique microstructure, presents the following advantages: (1) The porous structure may act as a reservoir for Li + ions storage and is optimal for the easy immersion and diffusion of the electrolyte, which can shorten the path lengths with less resistance for both Li + ion diffusion and electron transport within the electrolyte [73];…”
Section: Resultsmentioning
confidence: 99%
“…All catalytic activity data are analyzed in Table 2. Electrocatalytic activity is contrasted among the prepared N-CNTs, and doping of nitrogen enhances the ability of graphene sheets inside the carbon matrix to donate electrons, which is advantageous for O 2 electroreduction [37,38]. Remarkably, N-CNT(800) shows the most onset potential (E ORR ) of (0.91 V) and half-wave potential (E hw ) of (0.70 V), which are lower than those of 20% Pt/C electrodes [35].…”
Section: Electrochemically Catalytic Activitymentioning
confidence: 99%
“…Moreover, the well-matching layered structure between 2D MoS 2 and graphene not only increases the contact area for efficient charge transfer across the interface, but also exhibits better synergistic effects between two components, thereby greatly improving the electrochemical performances for HER and LIBs. In addition, N-doping of graphene can change the electron density in the graphene sheets, which provides an electrocatalytic surface [29][30][31]. Yang reported that the MoS 2 /RGO hybrid fabricated via a solvent-evaporation-assisted intercalation method exhibited the excellent HER performances due to the combined effects of abundance of exposed active edge sites and excellent internal electrical conductivity M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 4 [32].…”
Section: A N U S C R I P Tmentioning
confidence: 98%